Internalizing Multiculturalism Values Through Education: Anticipatory Strategies for Multicultural Problems and Intolerance in Indonesia - Firdaus Firdaus; Dian Kurnia Anggreta; Faishal Yasin (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
Diversity is a fact inherent in Indonesia, a country that consists of various ethnic groups, religions, cultures, and customs from Sabang to Merauke. But on the other hand, in many cases, this diversity can also threaten the integrity of Indonesia whose motto is “unity in diversity”. A lot of cultural friction to ethnic and religious conflicts has coloring the dynamics of Indonesian diversity from the Orde Lama era to the present. This is clearly a serious threat to Indonesia’s integrity. Since the Reformation era, the Indonesian government has adopted a multicultural approach to solvemulticultural issues. This paper describes the values of multiculturalism that can be used as a spirit in organizing the social system among a plural society. Education, both formal and informal, constitutes a strategic institution to internalize those values of multiculturalism. The research method uses a literature review, with a hermeneutic approach. The findings of this study, the process of internalizing multicultural values through education involves the environment, actors and schools. The success of the internalization process is determined by the mutual support between knowledge, process and acceptance of the values of multiculturalism.